2017
DOI: 10.1021/acscatal.7b00189
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Reactive Oxygen Species via Electroprotic Interaction of H2O2with ZrO2Gel: Ionic Sponge Effect and pH-Switchable Peroxidase- and Catalase-Like Activity

Abstract: Formation of reactive oxygen species (ROS) is of vital importance in catalytic oxidation chemistry. In this paper we have shown that a nonredox system such as amorphous zirconium dioxide (a-ZrO2) is highly active in ROS formation via H2O2 decomposition. Interaction between a-ZrO2 and H2O2 in aqueous solution was investigated by means of EPR, HYSCORE, Raman, and UV–vis, along with auxiliary FTIR, TG-MS, and XPS techniques, in a broad range of pH values and H2O2 concentrations. Various reaction intermediates suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 84 publications
(104 reference statements)
8
73
0
Order By: Relevance
“…Versatile metal oxide nanoparticles (MO NPs) have been extensively applied in various scientific and engineering fields such as electrochemical reactions, photocatalytic degradation, fuel cells, and photoreactions [1][2][3][4][5][6][7][8][9]. However, nanometer-sized MO NPs can easily penetrate the human body through the skin, and, thus, the biocompatibility of these nanoparticles (NPs) should be seriously considered as a safety measure [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Versatile metal oxide nanoparticles (MO NPs) have been extensively applied in various scientific and engineering fields such as electrochemical reactions, photocatalytic degradation, fuel cells, and photoreactions [1][2][3][4][5][6][7][8][9]. However, nanometer-sized MO NPs can easily penetrate the human body through the skin, and, thus, the biocompatibility of these nanoparticles (NPs) should be seriously considered as a safety measure [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The pH factor plays an important role in the reactions catalyzed by nanozymes. It was found that some nanozymes exhibited different enzyme activities at different pH values [70][71][72][73]; for example, if the pH of α-ZrO 2 is lower than 5.3, it shows the catalytic activity of peroxidase, and when the pH is higher than 5.3, it shows the catalytic activity of catalase [71]. Additionally, the temperature factor can also regulate the catalytic efficiency of nanozymes.…”
Section: Ph and Temperaturementioning
confidence: 99%
“…58,[66][67][68] Noteworthy, EPR spectroscopy is commonly applied to study the state of the paramagnetic active sites doped into the mesoporous hosts such as zeolites in various catalytic processes. [69][70][71][72] In the case of 1Mn, presented herein, the state of the Mn II sites was successfully monitored in the real time by employing in situ EPR spectroscopy during the sorption/desorption of water molecules. Structural and electronic changes within the coordination sphere of Mn II affects also the low-temperature photo-induced magnetization of the compound which is evidenced by detailed photomagnetic studies.…”
Section: Introductionmentioning
confidence: 99%